Borderline Personality Disorder A Case-Based Approach (Springer International Publishing, 2018)
This book brings together a series of experts and experienced clinicians to describe and discuss a series of BPD cases in a manner that emphasizes core descriptive and diagnostic features, principles and techniques, and key take-home messages for clinicians at all levels of experience. The book emphasizes consideration for the disorder from multiple perspectives to help identify effective responses to common clinical challenges and decision points. Written by experts in the field, each chapter uses a consistent format to present a common clinical challenge along with an effective therapeutic response and discussion of relevant theoretical and empirically validated principles. Each chapter title contains a patient's (fictionalized) name and a subheading identifying the clinical dilemma or approach to be illustrated. The text includes key points and chapter summaries to help pull together the most important takeaways as quick reference. Borderline Personality Disorder is a vital resource for psychiatrists, psychologists, psychiatric nurses, general internists, social workers, and all medical professions working with patients suffering from Borderline Personality Disorder.